Preparation of Ni-Ferrite Samples for Absorbing Spectrum of X-Band Waves Using Network Analyzer Method - T. John Ali, Hussein; A. Ammar, Assis. prof. Hashim; A. Yasser, prof. Hassan (مجلة كلية التربية, 2020)